دراسة تحليلية لواقع وتطور مدارس التعليم الثانوي بمحافظة اللاذقية في ضوء المعايير التربوية للخريطة المدرسية - طيوب, محمود; درويش, رمضان; حسين, محمود حسن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى دراسة الواقع الفعلي لمدارس التعليم الثانوي في محافظة اللاذقية, ودراسة تطورها عبر الزمن بغرض تحديد الاحتياجات الفعلية والمستقبلية من المدارس, لاستيعاب الأعداد المتزايدة من الطلاب, معتمداً في ذلك على المعايير الوطنية المعتمدة في الخريطة المدرسية السورية, ولتحقيق ذلك تمّ الاعتماد على البيانات الإحصائية لمرحلة التعليم الثانوي (أعداد المدارس, أعداد الشعب, أعداد الطلاب, أعداد المدرّسين), خلال الفترة 2006-2011, وتحليلها باستخدام الأساليب الإحصائية المناسبة. وبعد الدراسة والتحليل تمّ التوصل إلى النتائج الآتية: 1- تتزايد أعداد المدارس والشعب والطلاب والمدرّسين في مرحلة التعليم الثانوي بشكل مضطرد بالنسبة إلى الزمن. 2- يتصف الواقع الفعلي لمرحلة التعليم الثانوي بكفاية أعداد المدارس والشعب والمدرّسين , فهي تنخفض عن الحد الأدنى للمعايير التربوية المحددة في الخريطة المدرسية السورية , كما أن المحافظة ليست بحاجة إلى إنشاء مدارس ثانوية جديدة حتى العام 2025, إذا أخذنا بعين الاعتبار توزيع الأعداد المتزايدة من الطلاب خلال الفترة 2012-2025 على المدارس الموجودة فعلاً وبشكل تتحقق فيه المعايير التربوية للخريطة المدرسية بالمتوسط. 3- إن التجربة التي قامت بها وزارة التربية في محافظة اللاذقية (إنشاء مجمعات مدارس التعليم الثانوي في المحافظة والأرياف) وبشكل تراعي فيه التوزع الجغرافي والسكني للمناطق التعليمية في المحافظة, وسهولة وصول الطلاب إلى المدرسة أدت إلى إيجاد حلول كبيرة لمشكلة الازدحام في المدارس الثانوية. The research aims at studying actual fact of secondary schools in the province of Latakia, and its evolution over time in order to identify the actual needs and future of the schools, to accommodate the growing numbers of students, relying on national standards adopted in the Syrian school map. To achieve this, the relying was on statistical data of secondary education (the number of schools, the number of people, the number of students, number of teachers), during the period 2006-2011, and analyzing them using appropriate statistical techniques. After studying and analyzing, the research comes up with the following results: 1– Increase in the number of schools and people, students and teachers in secondary education steadily as regards time. 2- The actual reality of secondary educations stage is characterized by adequacy of the number of schools as well as people and teachers, as they fall below the minimum standards of education set out in the Syrian School Map, and the province does not need to create new secondary schools until the year 2025 if we take into account the distribution of the growing numbers of students during the period 2012-2025 to schools that already exist in a way that achieve the educational standards of the average school map. 3- The experiment which was conducted by the Ministry of Education in the province of Latakia (building up pools of secondary schools in the province and rural areas) in a way that takes into account the geographical distribution and the residential areas of education in the province, and ease of student access to school has lead to find significant solutions for the problem of overcrowding in secondary schools.